THE CORRELATION BETWEEN STUDENTS’ MOTIVATION AND VOCABULARY MASTERY - Anggun Rohepta (English Education Department Slamet Riyadi University Surakarta, 2020)
The aims of this research to find out the significant correlation between students’ motivationmand vocabulary mastery at the tenth gradeystudents of SMA N 1 Tangen Kabupaten Sragen in the 2019/2020 academic year.IThe researcher conducted a correlation research. Tomcollect the data the researcher held try-out and test. After collecting the data,jthe researcher analyzed the data using validity and reliability test.jThe calculating of the collected data showsmthat the coefficient of the correlation between students’omotivation (X) and vocabularybmastery (Y) was 0,130 with the level significant 5% for degreemof freedom (df) = 26 was 0,388 and the level significant 1% for degree of freedom (df) =26 was 0,496 which Ho = rxy < rtable, it means r observation (rxy) was lowest than rtable and it was concluded that the Null Hypothesis was accepted, there was a negative of significant correlation between students’ motivation (X) and vocabulary mastery(Y) was rejected. Therefore, the alternative hypothesis was rejected. It can bemconcluded that there is negativemcorrelation between students’wmotivation and vocabulary mastery at the tenth grade students of SMA N 1 Tangen Kabupaten Sragen in the 2019/2020 academic year.” Keyword: CorrelationmStudy, Students’mMotivation. VocabularymMastery. Quantitative.